If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-18=-9(b-2)
We move all terms to the left:
-18-(-9(b-2))=0
We calculate terms in parentheses: -(-9(b-2)), so:We get rid of parentheses
-9(b-2)
We multiply parentheses
-9b+18
Back to the equation:
-(-9b+18)
9b-18-18=0
We add all the numbers together, and all the variables
9b-36=0
We move all terms containing b to the left, all other terms to the right
9b=36
b=36/9
b=4
| 14+6t=7t+14 | | 4x+11/5=3/4 | | -4(x+2)-4=-12 | | -3b-4b=28 | | 5y-15=2y-27 | | F(x)=2x-16x+9 | | 2=-2(s-5) | | 4x+5/3=11/4 | | 18=16-b/6 | | 3=4+x/2 | | 4p-3=13( | | -1=4+x/6 | | v/5+17=17 | | q/6-10=-9 | | 3k-6=2k-1 | | X/2-8x;x=10 | | -5p+8=53 | | 2=z/6 | | 5x7=2x+23 | | (2x-x)2=225 | | -57=7x-10(9+x) | | 8^x=3 | | 72x=360 | | 6w-7w-2=8 | | 4w+60=10w | | 44=-5z+9z | | -36=4(q-8) | | 8+a/2=-2 | | 4x3+24x2+44x+4=0 | | -3=-3(d+5) | | -8(t-9)=88 | | 2(12+r)=10 |